Naïve Bayesian Classifier and Genetic Risk Score for Genetic Risk Prediction of a Categorical Trait: Not so Different after all! - Sebastiani, Paola; Solovieff, Nadia; Sun, Jenny (Frontiers in Genetics, 2012)
One of the most popular modeling approaches to genetic risk prediction is to use a summary of risk alleles in the form of an unweighted or a weighted genetic risk score, with weights that relate to the odds for the phenotype in carriers of the individual alleles. Recent contributions have proposed the use of Bayesian classification rules using Naïve Bayes classifiers. We examine the relation between the two approaches for genetic risk prediction and show that the methods are mathematically related. In addition, we study the properties of the two approaches and describe how they can be generalized to include various models of inheritance. The advantage of working with Naïve Bayes classifiers appears to be the generalizability to include interaction between different genetic variants and non-genetic risk factors and the probabilistic framework for marginal and conditional inference.